Design of Power Analyzer using LabVIEW. (January 2020) - Srikanth, S.; Mabhu Hussain, P.; Sridhar, P.
Abstract: Power analyzer is a device for analysis of power quality and measurement of various electrical quantities. Various power quality issues are raised in this because of the use of various non-linear loads. This paper proposes a virtual instrument for this function. the conventional measurement systems were not adequate for this purpose because they have no accurate method for deleting harmonics and ability to store data. We can overcome these difficulties by developing a virtual instrument. This is cost-effective as well as, convenient. LabVIEW provides a software platform for developing virtual instrument by acquiring current & voltage data through national instruments MyDAQ. LabVIEW provides good visualization and easy programming interface. The inputs to the proposed system are voltage and current and the hardware system developed, allows for measurement and analysis of system parameters such as power (active, reactive, apparent and instantaneous), power factor, Total Harmonic Distortion (THD) (%) and Signal-to-noise and distortion ratio (SINAD) in decibels using voltage and current. A hardware system is developed to acquire voltage and current data and work in convention with through software developed.